Desenvolvimento de um índice de sustentabilidade hidroambiental (Estudo de caso: APA de Baturité, Ceará) - Vieira, Paulo Márcio Souza (2014)
In order to support an integrated management policy and the rational use of water resources toward sustainable development, it is unavoidable the search of efficient instruments to measure the performance of hydrological and environmental systems. Indicators and indexes have the role of translating numerically one specific situation and point out to the decision maker the sustainability status of that region. The development of a hydro-environmental sustainability index complies a multidisciplinary analysis dealing with several interrelated aspects of hydrologic and environmental parameters, based on some important criteria such as: water availability, quality and use of water, people access to water, environment impact.To the development of such an index in the State of Ceará a representative area of the semiarid highland environment has been chosen: Baturité APA (Area of Environmental Protection).A model structure based on the Pression-State-Response approach has been considered, resulting in the proposition of a Hydro-Environmental Sustainability Index for the highlands in the Semiarid Brazilian Region